Early Childhood Character Education Utilizing Innovative Communication Media Wayang Beber Fable - Noegroho, Jati (LPPM Universitas Pahlawan Tuanku Tambusai, 2024)
This research uses the Wayang Beber Fable performance media. Fable stories attract the attention of young children. The goal is that Wayang Beber Fable can be used as an innovative medium for early childhood character education. Observations and interviews were carried out for data collection. The aim is to be able to evaluate teachers' difficulties. The evaluation results show that teachers lack teaching aids for character education. As a solution, workshops and performances are held for students. The workshop aims to learn how to play and make Wayang Beber Fable. The teachers succeeded in playing Wayang Beber Fable independently. This allows teachers to develop performance stories relevant to children's needs. Every Wayang Beber Fable performance always has a moral message in it. Early childhood needs moral teachings. At this stage, children learn to understand the world around them. Wayang Beber Fable can be an innovative medium for early childhood character education. It can even be integrated into a broader character education curriculum. Educators now have alternative media for character education teaching aids that are innovative and interactive.